''Tweaking'' potential research participants to meet clinical trial eligibility criteria: ethical concerns and scientific implications. (February 2011) - Henry, Blair; Lin, Yulia; Callum, Jeannie
In October 2010, we reported on an interesting clinical practice phenomenon in a Letter to the Editors of the New England Journal of Medicine [1] . In three separate clinical oncology studies, during the past year, it was discovered that select patients were being transfused blood products for the sole purpose of meeting inclusion criteria for enrolment in a clinical trial. These cases were detected after the recent introduction of prospective screening of all blood product requests by blood bank technologists at our institution, in attempts to promote the appropriate use of blood transfusion. Of note, in each case, the patients were young and dealing with advanced malignant disease that had failed all available therapies. The purposes of the letter were: to report on this practice and to determine if these were anomalous events or perhaps indicative of more frequent but unreported phenomena; and to outline what we felt were the ethical concerns raised by this practice. Unsurprisingly, we received a wide range of responses to our original letter. Many supported our concerns about the increased risk to patients and the potential adverse impact of the scientific findings when such a practice is tolerated; however, there were also responses that were critical of our recommendations. This article contribution provides us with an opportunity to further explore the implications of the practice we observed and hopefully continue this important ethical conversation.